Application of problem analysis and resolution methodology (MASP) in an automotive assembly industry - Gaigher, Hitalo Antunes; Feroni, Rita de Cassia (Brazilian Journal of Production Engineering, 2021)
The automotive sector has been growing rapidly. Thus, companies in the industry seek mechanisms to improve the management of their products and processes, in order to guarantee the achievement of goals and cost reduction. The present article, through action research, raised the causes of the high rate of lack of materials in the manufacturing process in an automotive manufacturer. The information related to the study was collected via the company’s information system and subsequently mapped and proposed solutions / actions for the causes of the problem. For that, some quality management tools were applied, such as Methodology for Analysis and Problem Solving - MASP, cause-effect diagram, five whys, 5W2H and checklist. As a result, it was possible to reduce the causes that directly caused supplier delays in the supply process, achieving, in the first seven months following the implementation of action plans, a 90.14% reduction in supplier delays, thus justifying the effectiveness of the actions proposed by the research.